2010
DOI: 10.1007/s12560-010-9048-z
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus Contamination of Bell Pepper from Handling During Harvesting and Packing

Abstract: To evaluate the impact of harvesting and packinghouse operation on the contamination of green bell pepper (GBP) with viruses and enteric bacteria. Hands of 97 workers plus 40 GBP were sampled from field and packinghouse areas. RT-nested PCR were used for the identification of Noroviruses (NV) and Chromogenic agar for the quantification of coliforms and Escherichia coli. NV was found in 30.9 and 23.7% of workers' hands, before and after 3 h of work, respectively, while 45 and 30% of field and packed GBP was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Of these, contaminated irrigation water has received the greatest attention. However, food handlers, particularly those for hand‐picked products, have been identified as important contributors to the overall microbiological quality of fresh produce (Leon‐Felix and others ). So has contamination with pathogens present in soil/biosolids (Seidu and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, contaminated irrigation water has received the greatest attention. However, food handlers, particularly those for hand‐picked products, have been identified as important contributors to the overall microbiological quality of fresh produce (Leon‐Felix and others ). So has contamination with pathogens present in soil/biosolids (Seidu and others ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the few studies looking for viruses in crops in northwest of Mexico was done by Leon‐Felix et al . . They looked for the presence of NoV in bell peppers using RT‐nested PCR and found the presence of NoV in 45% of the samples from the field and 30% from packed peppers (Leon‐Felix et al .…”
Section: Resultsmentioning
confidence: 99%
“…When studying the opposite route of transmission, they found that 14% of FCV could be transferred from lettuce to bare hands (Bidawid et al , 2004(Bidawid et al , , 2000a. This ease of reversible viral transfer between workers and produce was later supported in a fi eld study (León-Félix et al , 2010) evaluating the impact of harvesting and packinghouse operations on the contamination of green bell pepper with NoV. When testing the workers' hands for NoV before and after 3 hours of work, they were able to show a change in the rates of positivity of 0% to 14% for pickers, 53% to 33% for classifi ers and 45% to 25% for packers.…”
Section: Viruses In Soft Fruitsmentioning
confidence: 86%
“…Clear legislation on the use, handling and treatment of water applied in industrial fresh produce production should be effi cient to reduce the risk of pathogens from faecal contamination (EFSA BIOHAZ, 2011). Moreover, it has been shown that handling of fresh produce by workers during harvesting and packing is an important risk factor for not least NoV contamination of fresh produce (León-Félix et al , 2010). Implementation of improved hygienic measures is therefore needed in agricultural operations to avoid risk of viral contamination .…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation